2013
DOI: 10.1504/ijmdm.2013.054456
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the strategic relevance of organisational capabilities: evidence from Turkish hotels

Abstract: This study identified capabilities with links to strategic behaviour and performance in Turkish hotels. Executives in 111 Turkish hotels attached greater importance to market and market-linking capabilities than other capabilities. The generic strategy employed per the Miles and Snow typology was associated with differences in all the capabilities, with the greatest disparities seen among defenders. Although hotels tend to adopt the cost-leadership approach, differentiation was also associated with capability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 119 publications
(125 reference statements)
0
3
0
Order By: Relevance
“…In this research, and based on the literature that has been reviewed (Aburub, 2015; Nieves et al. , 2016; Zhang & Sharifi, 1999; Koseoglu, Parnell, & Topaloglu, 2013; Morgan, Kaleka, & Katsikeas, 2004; Lin & Wang, 2015), a new research model has been formulated as shown in Figure 1. This research model is presented and examined empirically in the context of the hotel sector.…”
Section: Research Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, and based on the literature that has been reviewed (Aburub, 2015; Nieves et al. , 2016; Zhang & Sharifi, 1999; Koseoglu, Parnell, & Topaloglu, 2013; Morgan, Kaleka, & Katsikeas, 2004; Lin & Wang, 2015), a new research model has been formulated as shown in Figure 1. This research model is presented and examined empirically in the context of the hotel sector.…”
Section: Research Modelmentioning
confidence: 99%
“…This construct includes three items. The measures of service differentiation were developed based on Koseoglu et al. (2013) and Morgan et al.…”
Section: Research Modelmentioning
confidence: 99%
See 1 more Smart Citation